College accounting - Price, John Ellis; Haddock, M. David; Brock, Horace R. (Boston : McGraw-Hill/Irwin, 2003)
Business
Keywords: College accounting; Business; Cash; Accounting principles; Merchandise inventory; Property; Bonds; Profit; Cost accounting